Electrochemical-Thermal Modeling to Evaluate Battery Thermal Management Strategies: I. Side Cooling. Issue 1 (1st January 2015) - Bandhauer, Todd; Garimella, Srinivas; Fuller, Thomas F.
Abstract : Thermal modeling of lithium-ion batteries is important for assessing the impact of different thermal management strategies on electrochemical performance. Existing models either do not correctly couple the electrochemical and thermal fields, or require significant computational resources that preclude rapid investigation of various cooling methods in hybrid electric vehicle (HEV) simulations. In this study, a fully coupled electrochemical-thermal model that utilizes temperature dependent experimental data is described for a single spirally wound lithium-ion cell within a larger battery pack. In the model, temperature, current, heat generation, and depth of discharge ( DOD ) are allowed to vary locally and with time. In Part I of this study, a two dimensional cross-section for two different cell designs (8 Ah and 20 Ah) is simulated with both air and liquid surface cooling using a dynamic power profile. The results show that although liquid cooling reduces peak temperature significantly, it imposes a temperature difference across the cell. This causes the current and, subsequently, DOD to vary locally, which may adversely impact the life of the cell. Furthermore, as the cell increases in size and power level, the imposed temperature and DOD differences grow. Neither air nor liquid cooling allowed the pack size to be reduced beyond factors of 2 or 4, respectively.